Conflict management in semiconductor companies.[article]. - Clamor, Ma. Regina Jose
This paper is a preliminary study on conflict management practices in the semiconductor industry. The study aimed to survey and describe what conflict management practices are being applied in the semiconductor industry, and to get a sense of what companies, particularly human resource managers, mean when they talk of conflict management practices, Heads of different human resource departments were interviewed for this purpose. The results show that most of the efforts at conflict management take the form of relationship-building and prevention of dysfunctional conflict. On the other band, functional conflict is facilitated through creative and structured communication machanisms. Specific conflict resolution mechanisms or approaches were not presented by the respondents. This may be due to the variety of conflict resolution approaches as well as the types, and sources of conflict that arise in these organizations. The result were discussed in relation to different conceptual approaches, namely of Walton(1987), Bisno(1988) and Brown(1983).